FOOD SECURITY OF THE EUROPEAN UNION AND THE INFLUENCE OF COVID-19 - Liviu MARCUȚĂ; Agatha POPESCU; Cristiana TINDECHE; Dragoș SMEDESCU; Alina MARCUȚĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food security is one of the basic elements of human security that can only be ensured through a sustainable development of society. On the other hand, food security is an important element of global and national security, and is ensured at European level through the common defence and security policies implemented by the Member States. And this food security, which for many countries in the world is already a difficult problem to manage, was affected in 2019 by the COVID-19 pandemic, which caused the whole world to face an unprecedented crisis and which, although it affected the whole world, had an even greater effect on the poor populations that suffered even more, amid an increase in hunger anyway for four consecutive years, that is in the period 2017-2020. In this paper we aimed to analyze the food security situation in European Union countries and how the Covid-19 crisis has affected it. Based on the data provided by international databases, the information was processed, analyzed so that conclusions can be drawn that highlighted the fact that food security is one of the issues of concern to decision makers internationally, but which is ensured for European Union countries this is due to the developed agricultural sector and the productions that manage to ensure the food needs of the European population. The analyzed indicators followed both the agricultural areas and the GDP value, but also the value of the imports and exports of agri-food products at the level of the member countries of the European Union.